Modified single rigid vacuum-formed indirect bonding trays for lingual bracket application: a case report - Nguyen Anh Viet; Nguyen Anh Thuy (Australasian Orthodontic Journal)
Lingual orthodontic treatment offers an aesthetic alternative but presents unique challenges in bracket positioning. The present article introduces a modified design and fabrication process for rigid vacuum-formed indirect bonding trays for lingual bracket application. The technique is presented through a clinical case report of an adult patient who presented with bimaxillary dentoalveolar protrusion and managed using lingual appliances, premolar extractions, and mini-screws. The modified rigid vacuum-formed trays enabled the accurate simultaneous bonding of multiple teeth as well as individual teeth. The technique offers several advantages over existing indirect bonding methods, including time-saving, simplicity, easy removal of excessive adhesive, and potential cost-effectiveness. The superimposition of post-bonding scans and the digital orthodontic setup showed high agreement between the planned and actual bracket positions. Additionally, the close alignment between the planned orthodontic setup and the achieved treatment outcome highlights the reliability of the technique for predictable lingual orthodontic treatment. Further clinical studies with larger sample sizes are needed to confirm the effectiveness of this technique.